2011
DOI: 10.5489/cuaj.10080
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic ratio is preserved for radiotherapy or cisplatin treatment in BRCA2-mutated prostate cancers

Abstract: Prostate cancers in patients with a mutation in BRCA2 have earlier disease onset and an aggressive course, often necessitating the use of systemic therapy. However, these tumours are DNA repair-defective and could respond favourably to Parp inhibitors or DNA-damaging agents, depending on the therapeutic ratio (ratio of tumour response to normal tissue toxicity). We describe 3 patients treated with precision radiotherapy or cisplatin who responded favourably to both agents, yet did not suffer undue toxicity. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Poly (ADP-ribose) polymerase inhibitors were originally developed to selectively target HR-defective cells, and have been tested as a monotherapy and in combination with an alkylating agent and cisplatin in patients with certain solid tumors. (36)(37)(38)(39) In this study, 3-AB, as a single agent, had minimal cytotoxic efficacy (Fig. 1a), and only modest increases of cH2AX and RAD51 focus formation in response to 3-AB were observed in the ESCC cells, as compared to the untreated controls (Figs 1b,4a).…”
Section: Discussionmentioning
confidence: 61%
“…Poly (ADP-ribose) polymerase inhibitors were originally developed to selectively target HR-defective cells, and have been tested as a monotherapy and in combination with an alkylating agent and cisplatin in patients with certain solid tumors. (36)(37)(38)(39) In this study, 3-AB, as a single agent, had minimal cytotoxic efficacy (Fig. 1a), and only modest increases of cH2AX and RAD51 focus formation in response to 3-AB were observed in the ESCC cells, as compared to the untreated controls (Figs 1b,4a).…”
Section: Discussionmentioning
confidence: 61%
“…As a potentially important biomarker of DNA repair status, recent reports have suggested that tumor cells that lack PTEN have a marked reduction in RAD51-dependent HR and are therefore sensitive to PARPi in vitro and in vivo (18-20). This suggests that many sporadic tumors could be amenable to PARPi-specific treatments or other agents that are highly toxic to HR-deficient tumor cells such as mitomycin C (MMC), cis-platinum (cDDP) and ionizing radiation (IR) (21-23). Novel trials utilizing PARPi in prostate and other cancers could therefore stratify patients on the basis of intact or abrogated function of the HR, FA, DDR (MRE11-ATM) and now, PTEN pathways (24-26).…”
Section: Introductionmentioning
confidence: 99%
“…In multiple reports consisting of germline BRCA mutated patients with breast cancer treated with radiation, no increased rates of acute or late toxicities were noted compared with sporadic breast cancer. 14 , 16 In addition, one case report by Vesprini et al 26 of 3 men with prostate cancer and germline BRCA2 mutations found no adverse short- or long-term gastrointestinal or genitourinary side effects after treatments with radiation and chemotherapy. Furthermore, cell lines generated from one of these BRCA2 mutated patients indicated no difference in clonogenic survival after radiation compared with normal fibroblast strains.…”
Section: Discussionmentioning
confidence: 99%